PRISMA Method For Predicting Breast Cancer - Neneng Intan (Jurnal Inovasi Informatika, 2021)
Breast cancer is one of the most common types of cancer in Indonesia. There are no definite symptoms that can be accurately diagnosed to detect breast cancer. Several studies on breast cancer have been carried out with various methods, but not all methods can predict breast cancer accurately. So the contribution of this research is to find a method that is accurate enough to detect breast cancer. This study uses the PRISMA method to find the right method for detecting breast cancer. The results show that the Naïve Bayes Classifier method is most often used because this algorithm is known to have a high level of accuracy with simple calculations and works very well compared to other classifier models. Another advantage is that this method only requires a small amount of training data to determine the parameter estimates needed in the classification process. Keywords : Breast Cancer, PRISMA, Naïve Bayes Classifier.